2009
DOI: 10.1142/s0217751x09043195
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of a Scalar Field on a Fuzzy Sphere

Abstract: The φ 4 real scalar field theory on a fuzzy sphere is studied numerically. We refine the phase diagram for this model where three distinct phases are known to exist: a uniformly ordered phase, a disordered phase, and a non-uniform ordered phase where the spatial SO(3) symmetry of the round sphere is spontaneously broken and which has no classical equivalent. The three coexistence lines between these phases, which meet at a triple point, are carefully located with particular attention paid to the one between th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
75
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(92 citation statements)
references
References 38 publications
13
75
1
Order By: Relevance
“…Comparing with previous studies of scalar field theories on fuzzy spaces [2,3] as well as the numerical results of [11,[17][18][19], we expect three phases: a symmetric single cut solution, in which the eigenvalue density has support on a single symmetric interval…”
Section: Phase Diagramsupporting
confidence: 62%
See 1 more Smart Citation
“…Comparing with previous studies of scalar field theories on fuzzy spaces [2,3] as well as the numerical results of [11,[17][18][19], we expect three phases: a symmetric single cut solution, in which the eigenvalue density has support on a single symmetric interval…”
Section: Phase Diagramsupporting
confidence: 62%
“…the numerical results of [21]. Scalar field theories on two-dimensional fuzzy spaces necessarily inherit this phase transition, and the straight line was found in the numerical studies of [11,[17][18][19] on the fuzzy sphere and the fuzzy disc. We reproduced this line by analytical methods.…”
Section: Comparison To Numerical Resultsmentioning
confidence: 91%
“…Several works [13,14,15,16,25,49] studied the phase structure of NC φ 4 theory in two dimensions, finding numerical evidence for a striped phase [50] characterized by non-uniform order. As an example, fig.…”
Section: Results For Nc Scalar Field Theorymentioning
confidence: 99%
“…This type of calculation has been carried out by Monte Carlo methods in a number of works [13,14,15,16,17] (including a very recent study of the entanglement entropy [18]). A different way to map NC scalar field theory in two dimensions to a finite-dimensional matrix model was introduced in ref.…”
Section: Methodsmentioning
confidence: 99%
“…The phase structure of non-commutative φ 4 in d = 2 and d = 3 using as a regulator the fuzzy sphere was studied extensively in [76][77][78][79][80][81][82]. It was confirmed that the phase diagram consists of three phases: a disordered phase, a uniform ordered phases and a non-uniform ordered phase which meet at a triple point.…”
Section: Introductionmentioning
confidence: 99%